A quick guide to social change buzzwords - Boolkin, Jay (Institutional Knowledge at Singapore Management University, 2017)
Social Impact, Intrapreneurship, Benefit Corporation, Shared Value— these are just a few of the many buzzwords that get thrown around in the social arena. But what do these terms mean and how do we apply them? JAY BOOLKIN of socialgoodstuff.com has come up with a handy guide that demystifies the myriad jargon and fanfare surrounding social change.